i'm trying to solve this question.

Find the sum of the Serias using Fixed-Point iteration: Q I should use Fixed-point iteration in order to find it. $P\ge1$.

Part B - Prove that the order of convergence R - of this serias - is unique(singularity). Proof by contradiction

I've seen this solution for Part A:

Lets call S - the sum, and try to find it. $$g(S)=S=\sqrt{p-(1-p)*S} \Rightarrow S^2 = p-(1-p)*S \Rightarrow S^2 + (1-p)*S-p=0$$ By so solving this quadratic equation we achieve $S=-1$ or $S=p$

This solution cancels S=-1, and says that S=p is the answer.

Couple of questions regarding this solution:

  1. Why is it ok to use Fixed-point iteration in order to find sum of a serias? Till now i've used Fixed-point iteration to find ROOTS of an equation.

  2. Why is it ok to assign random variable S g(S)=S and then say that solving this equation says that S is the sum?

  3. Why canceling the solution of $S=-1$?

  4. Part B - how is it possible to prove that order of convergence is unique? By definition, it's the first derivative that is not 0 in the root (probarely root=p).



There is no series, thus no sum of a series.

This is an expression with nested square roots, the sequence of finite, truncated expressions has (probably) a limit.

The range of the square root is the non-negative numbers, automatically disqualifying $-1$ from being the limit.

You need to prove the contractivity of $g$. Using elementary transformations and estimates you should be able to get $$ |g(S_1)-g(S_2)|\le\frac{p-1}{2\sqrt{2p-1}}|S_1-S_2| $$ You will need better estimates of the values that the iteration can reach to get contractivity for general $p>1$.

Convergence or divergence close to the fixed point is determined by if $|g'(p)|<1$. Now $g'(p)=\frac{p-1}{\sqrt{p+(p-1)p}}=1-\frac1p$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.